Methoxyl-containing hyper-crosslinked polymer from largely bio-based biphenyl methyl ether and its application in lithium-sulfur battery - Wale, Apparav K.; Das, Anoushka K.; Patil, Nita R.; Shelke, V. Manjusha; Ambade, V. Ashootosh; Wadgaonkar, Prakash P. (Reactive & Functional Polymers, 2025)
A new biphenyl methyl ether viz 2,2 `,3,3 `-tetramethoxy-5,5 `-bis(methoxymethyl)-1,1 `-biphenyl (TBMB) was synthesized starting from vanillin via three-step reaction sequence. The self-polycondensation of TBMB by employing two Bronsted acid catalysts, viz, p- toluenesulfonic acid (PTSA) and trifluoromethanesulfonic acid (TFSA) led to the formation of organic hyper-crosslinked polymers (HCPs) containing built-in methoxyl groups. HCPs were characterized by FTIR, solid state 13 C NMR, XPS, XRD, TGA, BET, and FESEM analysis techniques. HCPs synthesized using PTSA (HCP-PTSA) and TFSA (HCP-TFSA) exhibited a Brunauer-Emmett-Teller (BET) surface area of 480 +/- 5 and 590 +/- 4 m2/g, respectively and consisted of hierarchical pore structures with both micropores and mesopores. HCP-TFSA was evaluated as an active coating layer on conventional polypropylene (PP) separator in lithium-sulfur batteries to suppress the polysulfide shuttling on account of the ability of methoxyl groups to anchor soluble polysulfide species via coordination. The significant polysulfide adsorption capacity and improved cycling stability with a capacity of 617.2 mAh g- 1 at 0.5C and 99% capacity retention highlighted the potential of porous HCP containing built-in methoxyl groups in the development of attractive lithium-sulfur battery systems.
Keywords: Active coating layer; bio-based; Biphenyl methyl ether; Hyper-crosslinked polymer; lithium-sulfur battery; Methoxyl groups; Self-polycondensation

Methoxy substituted furan chalcones: an insight into anti-inflammatory, antioxidant, antidiabetic, antibacterial, and molecular docking studies - Ghorpade, Sujay A.; Kulkarni, Arati S.; Dandge, Padma B.; Chaugule, Hanmant N.; Ingle, Snehal S.; Bavi, Rohit S.; Bhosale, Raghunath B.; Peerzade, Nargisbano A.; Zaki, Magdi E. A.; Masand, Vijay H.; Patil, Nita R.; Jadhav, Shravan Y. (ChemistrySelect, 2026)
A series of methoxy-substituted furan-based chalcones (5a-m) were synthesized, characterized, and evaluated for in vitro anti-inflammatory, antioxidant, antidiabetic, and antibacterial activities. Among the series, compounds 5l, 5j, 5h, 5a, 5g, 5f, 5c, 5k, and 5e showed remarkable anti-inflammatory activity when compared to diclofenac sodium. The compounds 5k, 5e, 5m, 5h, and 5l showed outstanding activity in the DPPH free radical scavenging experiment, along with remarkable ferric ion reducing power activity in comparison to standard ascorbic acid. Compounds 5l, 5m, and 5g demonstrated significant alpha amylase inhibitory activity, comparable to that of the standard drug Acarbose, suggesting their potential as effective antidiabetic agents along with a good antibacterial profile against S. aureus and E. coli. The molecular docking studies revealed that compounds 5f and 5c showed the best docking profiles with BSA, while 5l and 5m demonstrated superior binding characteristics with amylase, highlighting their potential as promising bioactive candidates.
Keywords: Anti-inflammatory; Antibacterial; antidiabetic; Antioxidant; methoxy substituted furan chalcones; Molecular docking